HUBUNGAN INTERAKSI SOSIAL DENGAN KEPERCAYAAN DIRI SISWA KELAS X IPS - NABAHA, AHMAD YAZDAD (Jurnal Psikoedukasia, 2025)
The background that drives this research is that self-confidence is an aspect of personality that functions to encourage students to achieve success which is formed through the student's learning process in interaction with the environment. The problem in this study is whether there is a relationship between social interaction and self-confidence of class X IPS students of SMA N 1 Guntur Demak? The purpose of this study that the researcher wants to achieve is to determine the relationship between interaction and self-confidence in class X IPS students of SMA N 1 Guntur Demak.